A Two-Pillar Phillips Curve for Switzerland - Petra Gerlach-Kristen (Swiss Journal of Economics and Statistics, 2007)
Monetary aggregates have historically played an important role in Swiss monetary policy, with the Swiss National Bank using money growth targets until 1999. Since 2000, when a new policy framework was introduced that focuses on an inflation forecast, money growth has been used as an indicator variable. Given the continued reliance on monetary aggregates, the question arises how useful money growth is for explaining future price developments. Using Swiss data spanning 1979 to 2005, this paper estimates Phillips curve models that incorporate a measure of "trend" money growth. Using M3, we find that money growth impacts on inflation. M2, however, matters only if the downward shift in nominal interest rates over the sample is taken into account.
Keywords: E31; E42; E5; 330; inflation; money growth; Phillips curve; Switzerland